Vibro-acoustic and nonlinear analysis of cadavric femoral bone impaction in cavity preparations. (August 2018) - Oberst, Sebastian; Baetz, Johanna; Campbell, Graeme; Lampe, Frank; Lai, Joseph C.S.; Hoffmann, Norbert; Morlock, Michael
Highlights: We show for the first time the extraction of vibro-acoustic transfer functions of recorded impaction and acoustic radiation data during a cadavric study in a hip stem cavity preparation process. The application of nonlinear time series analysis to the impulse response functions shows that the data become higher dimensional and more complex after the forth broach. Vibro-acoustic cues have the potential to be used during intra-operative medical procedures as means of non-intrusive quality control. Graphical abstract: Abstract: Owing to an ageing population, the impact of unhealthy lifestyle, or simply congenital or gender specific issues (dysplasia), degenerative bone and joint disease (osteoarthritis) at the hip pose an increasing problem in many countries. Osteoarthritis is painful and causes mobility restrictions; amelioration is often only achieved by replacing the complete hip joint in a total hip arthroplasty (THA). Despite significant orthopaedic progress related to THA, the success of the surgical process relies heavily on the judgement, experience, skills and techniques used of the surgeon. One common way of implanting the stem into the femur is press fitting uncemented stem designs into a prepared cavity. By using a range of compaction broaches, which are impacted into the femur, the cavity for the implant is formed. However, the surgeon decides whether to change the size of the broach, how hard and fast it is impacted or when to stop the excavation process, merely based on acoustic, haptic or visual cues which are subjective. It is known that non-ideal cavity preparations increase the risk of peri-prosthetic fractures especially in elderly people. This study reports on a simulated hip replacement surgery on a cadaver and the analysis of impaction forces and the microphone signals during compaction. The recorded transient signals of impaction forces and acoustic pressures ( ≈ 80 µs–2 ms) are statistically analysed for their trend, which shows increasing heteroscedasticity in the force-pressure relationship between broach sizes. Tikhonov regularisation, as inverse deconvolution technique, is applied to calculate the acoustic transfer functions from the acoustic responses and their mechanical impacts. The extracted spectra highlight that system characteristics altered during the cavity preparation process: in the high-frequency range the number of resonances increased with impacts and broach size. By applying nonlinear time series analysis the system dynamics increase in complexity and demand for a larger minimum embedding dimension. The growing number of resonances with similar level of the transfer function indicates a higher propensity to dissipate energy as sound; the change in embedding dimension indicates a decrease in linearity. The spectral changes as well as the embedding dimension changes indicate either an improved coupling between the bone and the broach or the onset of micro-fractures caused by growing stress levels within the bone.